Pertanggungjawaban Tindak Pidana Korupsi yang dilakukan oleh Aparatur Sipil Negara - Gusta Andini, Orin; Marinda, Fitrah; Hamdani, Khulaifi (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2022)
The civil servants is the actor with the most corruption cases in the first semester of 2021. With its status as a state civil apparatus, including the law enforcement profession, it should receive more severe criminal sanctions. The criminal case in decision number 10/PID.TPK/2021/PT DKI. precisely without weighting. In addition, the judge's consideration of gender status where the perpetrator is a woman leads to considerations that relieve the perpetrator. This writing uses a normative research method with a case approach and a statutory approach. The analysis was carried out on library materials or secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials The results of the analysis were then described in a qualitative descriptive manner. The results of the study indicate that the accountability for criminal acts of corruption committed by state civil servants should be given weight by referring to the provisions of Article 52 of the Criminal Code (KUHP) so that the punishment in case number 10/PID.TPK/2021/PT DKI is not in line with the spirit of eradicating corruption, which should be aimed at providing a deterrent effect, both specifically and in general. Keywords: civil servants, corruption, penal